2023
DOI: 10.3390/ijms241411376
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera Lam. Isothiocyanate Quinazolinone Derivatives Inhibit U251 Glioma Cell Proliferation through Cell Cycle Regulation and Apoptosis Induction

Abstract: A major active constituent of Moringa oleifera Lam. is 4-[(α-L-rhamnose oxy) benzyl] isothiocyanate (MITC). To broaden MITC’s application and improve its biological activity, we synthesized a series of MITC quinazolinone derivatives and evaluated their anticancer activity. The anticancer effects and mechanisms of the compound with the most potent anticancer activity were investigated further. Among 16 MITC quinazolinone derivatives which were analyzed, MITC-12 significantly inhibited the growth of U251, A375, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The effects of MG on glioma cells were shown to be time- and dose-dependent, as reported by Xie et al (2023). They found that MG stimulated tumor cell apoptosis in a manner similar to the previously explained mechanisms without causing harm to normal human gastric mucosal cells [ 76 ]. MIC-mediated activation of apoptotic genes, including caspase, p53, Akt/MAPK, and Bax of the proapoptotic Bcl family, has also been observed in human prostate [ 77 ], liver [ 78 ], and neuroblastoma cancer cells [ 79 ].…”
Section: Antitumor Activities Of Isothiocyanatesmentioning
confidence: 77%
“…The effects of MG on glioma cells were shown to be time- and dose-dependent, as reported by Xie et al (2023). They found that MG stimulated tumor cell apoptosis in a manner similar to the previously explained mechanisms without causing harm to normal human gastric mucosal cells [ 76 ]. MIC-mediated activation of apoptotic genes, including caspase, p53, Akt/MAPK, and Bax of the proapoptotic Bcl family, has also been observed in human prostate [ 77 ], liver [ 78 ], and neuroblastoma cancer cells [ 79 ].…”
Section: Antitumor Activities Of Isothiocyanatesmentioning
confidence: 77%
“…MITC-12 induced apoptosis of U251 cells and increased the expression levels of caspase-3 and the Bax:Bcl-2 ratio. MITC-12 inhibits the proliferation of U251 cells, by arresting the cell cycle, activating JNK, and regulating cell cycle-related proteins Xie et al (2023) Glucomoringin isothiocyanate from M. oleifera seeds…”
Section: Antipsoriatic Activitymentioning
confidence: 99%
“…Studies have reported that MITC has anticancer, anti-inflammatory, cardiometabolic repair, nervous system protection, blood lipid regulation and diabetes prevention activities [26,27] . MITC are organic compounds with an (R N=C=S) group in their structures, but their biological activity and chemical stability are higher than those of isothiocyanate compounds in other plants due to the presence of aromatic rings and rhamnoses, among which 4-[(α -L-rhamnoxyl) benzyl] isothiocyanate has the highest content and the best activity [28] .…”
Section: Introductionmentioning
confidence: 99%